Changes in the engineering properties of marble in fire-exposed columns - Koca, M.Y.; Ozden, G.; Yavuz, A.B.; Kincal, C.; Onargan, T.; Kucuk, K. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2006)
Two marble columns in the bottom floor of a school building were exposed to intensive heat in the fire, and were subject of a debate about their load-carrying capacity following the event. After their removal from their original spots, series of tests on column samples were carried out to investigate variations in their engineering characteristics due to fire hazard. The temperature at the surface of the marble columns hit by the flames directly during the fire was estimated to be on the order of 500 °C using an empirically established relationship between porosity and temperature on intact marble core samples. Results of mechanical tests indicated that marble columns were still holding a significant load-carrying capacity despite 23% loss of strength at fire temperature. The spallings at the corners of the blocks forced the board of education to give the decision of replacing the gray marble columns with steel members. Occurrence of these spallings is attributed to stress concentrations and widening of micro fractures. Based on the results of mechanical, physical and chemical tests, a methodology to assess influence of fire hazard on marble and similar geological materials was developed.